Characterization of a Time-Domain Dual Lifetime Referencing pCO2 Optode and Deployment as a High-Resolution Underway Sensor across the High Latitude North Atlantic Ocean - Clarke, Jennifer S.; Humphreys, Matthew P.; Tynan, Eithne; Kitidis, Vassilis; Brown, Ian; Mowlem, Matthew; Achterberg, Eric P. (Frontiers in Marine Science, 2017)
The ocean is a major sink for anthropogenic carbon dioxide (CO2), with the CO2 uptake causing changes to ocean chemistry. To monitor these changes and provide a chemical background for biological and biogeochemical studies, high quality partial pressure of CO2 (pCO2) sensors are required, with suitable accuracy and precision for ocean measurements. Optodes have the potential to measure in situ pCO2 without the need for wet chemicals or bulky gas equilibration chambers that are typically used in pCO2 systems. However, optodes are still in an early developmental stage compared to more established equilibrator-based pCO2 systems. In this study we performed a laboratory-based characterization of a time-domain dual lifetime referencing pCO2 optode system. The pCO2 optode spot was illuminated with low intensity light (0.2 mA, 0.72 mW) to minimize spot photobleaching. The spot was calibrated using an experimental gas calibration rig prior to deployment, with a determined response time (τ63) of 50 seconds at 25 °C. The pCO2 optode was deployed as an autonomous shipboard underway system across the high latitude North Atlantic Ocean with a resolution of ca.10 measurements per hour. The optode data was validated with a secondary shipboard equilibrator-based infrared pCO2 instrument, and pCO2 calculated from discrete samples of dissolved inorganic carbon and total alkalinity. Further verification of the pCO2 optode data was achieved using complimentary variables such as nutrients and dissolved oxygen. The shipboard precision of the pCO2 sensor was 9.5 μatm determined both from repeat measurements of certified reference materials and from the standard deviation of seawater measurements while on station. Finally, the optode deployment data was used to evaluate the physical and biogeochemical controls on pCO2.